THE INFLUENCE OF SOME TECHNOLOGICAL FACTORS ON THE FUNCTIONAL FOOD CHARACTERISTICS OF CARROTS IN THE HILLY AREA OF TRANSYLVANIA - DORDAI, Lucian; ROMAN, Cecilia; ROMAN, Marius; NAGHIU, Anca (Studia Universitatis Babeș-Bolyai Chemia, 2021)
The global warming and aridization process in Romania presents zonal risk situations that can strongly affect the production potential and quality of carrot crops. An experiment was designed which follows the effect of technological factors on the quantity and quality of production for three varieties of carrots (Royal Chantenay, Atomic Red and Purple Haze F1), under organic cultivation conditions. 18 carrot samples were analyzed to evaluate the antioxidant capacity and total of mineral elements. For the antioxidant capacity a photochemiluminescence methods was used and the Photochem instrument from AnalytikJena togheter the ACL kit and for the total content of mineral elements was used the ICP-MS Elan Drc II Perkin-Elmer. By irrigating the carrot culture, the antioxidant capacity increases by 17.6% compared to the control sample (non-irrigated). Through chemical fertilization and zeolite fertilization of carrot culture, the antioxidant capacity increases by 3.2% and 18.8%, respectively, compared to the control sample (basic fertilization). By irrigating the carrot culture, the total content of mineral elements increases by 14.1% compared to the control sample (non-irrigated). Through chemical fertilization and fertilization with zeolite of carrot culture, the total content of minerals elements increases by 5.5% and 18.9% respectively with the control sample (basic fertilization).